Outage probability analysis of EH NOMA system network over Rayleigh fading channel using selection combining at the receiver - Phu Tran Tin; Minh Tran; Tran Thanh Trang (Bulletin of Electrical Engineering and Informatics, 2020)
Non-orthogonal multiple access (NOMA) with advantages such as superior spectral efficiency has been considered as a promising multiple access technique for the fifth-generation (5G) mobile networks. In this research, we propose energy harvesting (EH) NOMA system relaying network over Rayleigh fading channel using selection combining at the receiver. Firstly, we investigate the system performance in terms of the closed-form expression of the outage probability (OP). Here we compare the OP of two destination users of the proposed system. Finally, all the results is convinced by the Monte Carlo simulation. From the results, we can confirm that all the analytical and simulation results are the same in connection with the primary system parameters.